Prevalence Rates of Chlamydia Trachomatis and Other Sexually Transmitted Organisms in Infertile Couples Attending a Tertiary Medical Centre in Malaysia - A, Umi Kalsom; B, Suvra; RMR, Zainul; O, Siti Norlia; I, Zalina; S, Anita (IIUM Medical Journal Malaysia, 2020)
INTRODUCTION: Chlamydia trachomatis (CT), Neisseria gonorrhoeae (NG), Trichomonas vaginalis (TV) and Mycoplasma genitalium (MG) infections are well recognized and prevalent sexually transmitted infections (STIs). The role of Mycoplasma spp and Ureaplasma spp are still controversial as some are commensals of genitourinary tract. OBJECTIVES: To estimate the prevalence rate of 7 organisms: Chlamydia trachomatis, Neisseria gonorrhoea, Mycoplasma genitalium, Trichomonas vaginalis, Mycoplasma hominis, Ureaplasma urealyticum (UU) and Ureaplasma parvum (UP) in infertile married couples during infertility evaluation. MATERIALS & METHODS: A total of 274 samples from all of the 137 couples who attended the reproductive center from June to December 2014 were collected. Detection of the organisms was performed using multiplex polymerase chain reaction. RESULTS: STI-associated organisms were detected in 35.4% (97/274) of subjects. The prevalence rates of CT, MG, TV, UU, MH were 7.3%,1.1%, 0.4%,5.4% and 5.1% respectively. Twenty-one (7.7%) subjects were positive for more than one organism. 24/274 (8.8%) of subjects had history of urogenital tract-related symptoms and 50% (12/24) were tested positive to one or more organisms. The presence of symptoms in both male and female subjects were found to be 10% (2/20) in CT infection, 10% (7/67) in UP, 14% (2/14) in MH and 13% (2/15) in UU infections. CONCLUSION: Sexually transmitted organisms were detected in one third of subjects planning for fertility evaluation. The absence of symptom in most subjects particularly in CT infection emphasizes the need for microbiological screening during infertility evaluation. The presence of genital ureaplasmas and mycoplasmas in infertile couples should not be neglected. There is a growing need to clarify whether their roles are simply colonizers or pathogens implicated in infertility.